Mean Platelet Volume and Platelet Distribution Width in Patients With Obstructive Sleep Apnea Syndrome and Concurrent Chronic Obstructive Pulmonary Disease. (November 2018) - Archontogeorgis, Kostas; Voulgaris, Athanasios; Papanas, Nikolaos; Nena, Evangelia; Froudarakis, Marios; Mikhailidis, Dimitri P.; Steiropoulos, Paschalis
Evidence suggests that there is platelet activation in obstructive sleep apnea syndrome (OSAS) and chronic obstructive pulmonary disease (COPD). Our objective is to evaluate mean platelet volume (MPV) and platelet distribution width (PDW) in patients with overlap syndrome (OS), that is, concurrent COPD with OSAS. Mean platelet volume and PDW were assessed in consecutive patients who had undergone polysomnography and pulmonary function testing. They were divided into the following groups: controls (apnea–hypopnea index [AHI] <5/hour, and forced expiratory volume in 1st second [FEV1 ]/forced vital capacity [FVC] >70%), OSAS group (AHI ≥5/hour and FEV1 /FVC >70%), and OS group (AHI ≥5/hour and FEV1 /FVC <70%). A total of 485 patients (360 males and 125 females) were included. Mean platelet volume in controls was lower compared with the other groups: 10 ± 0.9 fL for controls versus 10.3 ± 1.2 fL for OSAS ( P = .006), versus 10.7 ± 1 fL for OS ( P < .001). Additionally, MPV was higher in OS group than OSAS: 10.7 ± 1 fL versus 10.3 ± 1.2 fL, respectively ( P = .002). Platelet distribution width was lower in controls compared with the other groups: 12.9 ± 2 fL for controls versus 13.6 ± 1.9 fL for OSAS ( P = .007), versus 13.8 ± 2.3 fL for OS ( P = .008), while there was no difference between OS and OSAS groups. Mean platelet volume and PDW are increased in patients with OS compared with healthy controls, with respiratory function being the major contributor in platelet activation in this series.